Gender and imprisonment in Thailand: Exploring the trends and understanding the drivers. (June 2016) - Jeffries, Samantha; Chuenurah, Chontit
Abstract: In this paper we explore and offer possible explanations for trends in the incarceration of women and men in Thailand from 2003 to 2013. Women in Thailand are far less likely than men to be in prison but fluctuations in incarceration saw gender gaps expand/contract over the decade. Exploration of variation in the composition of prison populations, arrest and sentencing suggest that regardless of gender, changing responses to less serious types of offending, especially drug crimes, are driving incarceration. More broadly, rather than any fundamental transformation in the offending of women or men per sea, imprisonment is being impacted by shifts in law, policy and criminal justice practice. War on drugs' policies, changes to parole and use of the Royal Pardon provide plausible explanations for the trends we report. The question of whether or not women have been disproportionately impacted by Thailand's punitive approach to drug crime is also explored.